Fabrication of highly conductive stretchable textile with silver nanoparticles. Issue 10 (June 2016) - Ashayer-Soltani, Roya; Hunt, Christopher; Thomas, Owen
A method has been developed for the deposition of conductive metals onto fibers within textile structures. The resultant fabric exhibited full metal coverage with good adhesion to the fibers. As well as being conductive and extremely flexible with little effect on its handle and drape properties. In order to make a conductive fabric, cotton was first mercerized followed by immersion in poly(diallyldimethylammonium chloride) solution. Silver nitrate was then reduced on the surface of the fabric which allowed formation of silver nanoparticles. Scanning electron microscopy studies of the conductive fabric confirmed the deposition of the polymer resulted in more uniform attachment of nanosilver to the surface of fibers. The fabric was then electroless plated to obtain a surface resistivity less than 0.2 Ω/square. This method can be used for woven, non-woven and knitted types of fabric. It can be applied on to the fibers before or after being made into a textile.